Peningkatan Kemandirian Belajar Siswa SekolahDasarMelaluiPenerapan Model Problem Based Learning (PBL - Suparman, Muh. Nasrul (Global Journal Teaching Professional, 2023)
Abstract This research is motivated by the learning difficulties that students still experience, namely their low learning independence during the implementation of the learning process at school. This research aims to determine student learning independence through the application of the Problem Based Learning (PBL) learning model in thematic learning in classVI -A of SD Negeri 24 Salemba. This research is Classroom Action Research (PTK) which uses aqualitative approach and qualitative descriptive methods. The subjectsinthis research were 23 students in class VI -A of SD Negeri 24 Salemba. The data in this research was obtained through observation, questionnaires and documentation. The research results showed that at thepre-cycle stage, student learning independence was in the lowcategory with an average of only 60%. IncycleI there was as lightincreasein student learning independence to 65%. Then in cycleII again there was a significant in crease in student learning to 80%. Base donthe research that has been conducted, it can be concluded that there has been a significant in crease in student learning independence in class VI- A of SD Negeri 24 Salemba through the application of the Problem Based Learning (PBL) model.